Pengembangan Kurikulum Pendidikan Islam - Ahmad Taufik (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
One component of education as a system is material. Educational material is all learning material delivered to students in an institutional education system. This educational material is better known as the curriculum. While the curriculum refers to material that has been systematically prepared to achieve the goals set.the curriculum must contain Islamic values ​​that are intrinsic and extrinsic capable of realizing the objectives of Islamic education. The concept of Islamic education is an effort directed at the formation of a child's personality in accordance with Islamic teachings or an effort with Islamic teachings, thinking, deciding and acting based on Islamic values.